From Work Well-Being to Burnout: A Hypothetical Phase Model - Morera, L. P.; Gallea, J. I.; Trógolo, M. A.; Guido, M. E.; Medrano, L. A. (Frontiers in Neuroscience, 2020)
Upon exposure to a chronic stressor, how individuals move from a healthy to a burnout state? Strikingly in literature has prevailed a categorical view rather than a dimensional one, thus the underlying process that explains the transition from one state to another remains unclear.The aims of the present study were (a) to examine intermediate states between work engagement and burnout using cluster analysis, and (b) to examine cortisol differences across these states. Two-hundred and eighty-one Argentine workers completed self-report measures of work engagement and burnout. Salivary cortisol was measured at three time-points: immediately after awakening and 30 and 40 minutes thereafter. Results showed four different states based on the scores in cynicism, exhaustion, vigor, and dedication: engaged, strained, cynical and burned-out. Cortisol levels were found to be moderate in the engaged state, increased in the strained and cynical states, and decreased in the burned-out state. The